Effectiveness of a selective If channel inhibitor ivabradine in patients with stable angina - E. V. Kuleshova (Кардиоваскулярная терапия и профилактика)
Aim. To study clinical effectiveness of ivabradine (7,5 mg twice a day) as a part of combined therapy, and its effects on physical stress (PS) tolerability in patients with Functional Class (FC) II-III stable angina and absolute or relative contraindications to beta-adrenoblockers (BAB).Material and methods. In total, 16 patients with FC II-III stable angina were examined. The examination included the assessment of angina attack incidence and need for short-acting nitrates, as well as treadmill test or 24-hour electrocardiography (ECG) monitoring.Results. Adding ivabradine to combined therapy or changing BAB to ivabradine is associated with a significant reduction in angina attach incidence, need for short-acting nitrates, heart rate at rest and at maximal PS, and total duration of myocardial ischemia, as well as with improved PS tolerability and cardiovascular system efficiency.Conclusion. In patients with absolute or relative contraindications to BAB or with poor BAB tolerability, a selective If channel inhibitor ivabradine improved clinical course of stable angina, stress test results and 24-hour ECG monitoring parameters.